. Guarantees of an independent tribunal in administrative proceedings in the context of the implementation of the human right to a fair trial - Гордєєв, Віталій Володимирович; Gordieiev, Vitalii; Sopilko I., Timush D., Vynohradova A., Zubko Ye., Gordieiev V. (My University, 2022)
Abstract The purpose of the article was to identify problem areas to ensure an independent court in administrative proceedings in the context of the implementation of the human right to a fair trial. The research was conducted using general scientific (induction, analysis, synthesis) and special legal (formal-logical, dogmatic, comparative-legal) methods. The authors have determined relevant areas of court staffing, such as: providing judicial power; providing administrative positions for the court and judicial staffing. It is stated that the improvement of legislation in the judicial sphere must be carried out from the inadmissibility of its exclusively positivist interpretation. It is concluded that, in order to guarantee the immunity of a judge in a broad context, it is important to prevent cases of unjustified disciplinary proceedings against judges. An important guarantee of the legality of the disciplinary liability of a judge is the observance by the subject of disciplinary liability of the due process established by law. It is emphasized that this is an assessment by the administrative court of the circumstances on which the plaintiff bases his claims in cases of appeal against these acts of the High Council of Justice
Keywords: human rights; right to a fair trial; administrative proceedings; independent tribunal; immunity